PENERAPAN METODE MAKE A MATCH UNTUK MENINGKATKAN KEMAMPUAN MENULIS PANTUN PADA SISWA KELAS VII SMP NEGERI 1 LAWE ALAS - Sa’adah Sa’adah; Irfan Johari (STKIP USMAN SAFRI KUTACANE, 2022)
This study aims to determine the improvement of rhyme writing skills through the application of the make a match method to class VII students of SMP Negeri 1 Lawe Alas in the 2021/2022 academic year. As for the population in this study were all students of class VII totaling 43 people and a sample of 22 people. The method used in this study is an experimental method with a one group pretest and posttest design with data analysis using the